2019
DOI: 10.52490/jeskape.v3i1.441
|View full text |Cite
|
Sign up to set email alerts
|

Etika Marketing Dalam Perspektif Ekonomi Islam

Abstract: Marketing is a human activity that is directed to meet the needs and desires through the exchange process. While marketing in the view of Islam is an application of strategic discipline in accordance with sharia values ​​and principles. Assessment of business success is not only determined by increasing economic and financial achievements, but success must also be measured through benchmarks of morality and ethical values ​​on the basis of social values ​​in religion. The type of this research is library resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Dengan ini para pengusaha harus memahami tantangan yang sangat penting ketika terlibat dalam pemasaran digital (e-commerce) harus sesuai dengan prinsip-prinsip Islam. Tantangan dari permasalahan tersebut antara lain yaitu, permasalahan legalitas, branding, dan apakah suatu produk halal atau haram (Malahayatie & Maryamah, 2019).…”
Section: Pendahuluanunclassified
“…Dengan ini para pengusaha harus memahami tantangan yang sangat penting ketika terlibat dalam pemasaran digital (e-commerce) harus sesuai dengan prinsip-prinsip Islam. Tantangan dari permasalahan tersebut antara lain yaitu, permasalahan legalitas, branding, dan apakah suatu produk halal atau haram (Malahayatie & Maryamah, 2019).…”
Section: Pendahuluanunclassified
“…The pleasure that arises from this satisfaction can help the poor. [39] Especially it can be an example and encouragement for other group members to increase their interest in paying agricultural zakat. Satisfaction is also obtained because the muzakki to gives directly to the desired mustahik.…”
Section: B Factors Affecting Zakat and Tax Paymentsmentioning
confidence: 99%
“…This research found that the identity formed in Ukrainian domestic society tends to see Western values such as protection of human rights, tolerance of other cultures, freedom of religion, individual freedom, and democracy, as well as social welfare as positive references (Princess, 2020). In the context of business ethics, research on ethical behavior in Islamic marketing shows that an entrepreneur in the view of Islam does not only seek profit, but seeks blessings, namely business stability by obtaining reasonable profits and getting the pleasure of Allah SWT (Malahayatie, 2019). Islamic business ethics are also considered as values that are directly related to religion (Pratiwi & Yusuf, 2021).…”
Section: Introductionmentioning
confidence: 99%